DALUWARSA DALAM PENUNTUTAN PIDANA PERSPEKTIF HUKUM PIDANA ISLAM - Firdaus Firdaus (Prodi Hukum Pidana Islam Fakultas Syari’ah dan Hukum Universitas Islam Negeri Sunan Ampel Surabaya, 2016)
Abstract: This article discusses the different point of view among the Muslim scholars about whether expired can abolish the punishment or not according to Islamic criminal law. Majority of Muslim scholars view that it cannot abolish the punishment. For those who hold the principle of expiry, they do not consider it as a penalty cancellation for entire jarîmah. Islamic law sees expired is only included to cancel the right to carry out the sentence. Thus, in the perspective of Islamic criminal law, any persons who have committed a crime and it has not yet sentenced and has already expired, it does not mean that the criminal is not removed. This means that a person who commits criminal act and it is prosecuted at any times, so the case can be tried. While the expired is valid only when the crime carried out by someone has got the judge's ruling, so that the perpetrator is serving as the judge ousted.Keywords: Expired, criminal prosecution, Islamic Criminal Law. Abstrak: Artikel ini membahas tentang daluarsa dalam penuntutan pidana perspektif hukum pidana Islam. Dalam hukum pidana Islam, di kalangan Ulama masih diperselisihkan, apakah daluwarsa dapat menghapuskan hukuman atau tidak. Menurut kebanyakan fuqaha, daluarsa tidak menghapuskan hukuman bagi seluruh jarîmah. Daluwarsa hanya masuk dalam bagian yang menghapuskan hak untuk melaksanakan hukuman. Dengan demikian, dalam perspektif hukum pidana Islam, setiap orang yang telah melakukan tindak pidana dan terhadap perbuatan pidana itu belum sampai dijatuhi hukuman, maka meskipun sudah daluwarsa, pidana tidak menjadi hapus. Ini berarti orang yang melakukan tindak pidana kapan waktu saja dapat dituntut atau perkaranya dapat diadili. Sedangkan daluwarsa hanya berlaku manakala tindak pidana yang telah dilakukan seseorang itu telah mendapat putusan hakim sehingga orang tersebut harus menjalani hukuman sebagaimana yang telah dijatuhkan hakim.Kata Kunci: Daluarsa, penuntutan pidana, hukum pidana Islam.